2012
DOI: 10.21829/azm.2012.281818
|View full text |Cite
|
Sign up to set email alerts
|

Population status of jaguars (Panthera onca) and pumas (Puma concolor) in northeastern Sonora, Mexico

Abstract: ABSTRACT. Jaguars are endangered in Mexico and the United States, necessitating careful monitoring of population status. We determined minimum numbers of jaguars and sympatric pumas in a small population in northern Sonora, Mexico, the nearest known breeding population to the United States, by photographic captures supplemented by idiosyncratic features of tracks from track surveys (1999)(2000)(2001)(2002)(2003)(2004)(2005). We also developed a discriminant function to differentiate species (jaguar v. puma) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 23 publications
0
10
0
5
Order By: Relevance
“…This area is situated close to the northern limit of the species' range and is probably more vulnerable to stochastic demographic effects (Vucetich & Waite 2003;Chavéz et al 2005). Additionally, the Yucatan Peninsula population is connected northward to areas with groups of individuals that occur at the lowest densities reported for jaguars, including the relict populations of Sinaloa and Baja California (Navarro-Serment et al 2005, Rosas-Rosas & Bender 2012) (see Figure 1A). Jaguars have been extirpated to the south of the Yucatan, in parts of Nicaragua and Honduras, and this loss may have disrupted the gene flow with individuals from further south (Sanderson et al 2002).…”
Section: Genetic Effects Of Habitat Deterioration and Biogeographymentioning
confidence: 99%
“…This area is situated close to the northern limit of the species' range and is probably more vulnerable to stochastic demographic effects (Vucetich & Waite 2003;Chavéz et al 2005). Additionally, the Yucatan Peninsula population is connected northward to areas with groups of individuals that occur at the lowest densities reported for jaguars, including the relict populations of Sinaloa and Baja California (Navarro-Serment et al 2005, Rosas-Rosas & Bender 2012) (see Figure 1A). Jaguars have been extirpated to the south of the Yucatan, in parts of Nicaragua and Honduras, and this loss may have disrupted the gene flow with individuals from further south (Sanderson et al 2002).…”
Section: Genetic Effects Of Habitat Deterioration and Biogeographymentioning
confidence: 99%
“…Estimates of jaguar numbers in Sonora, Mexico, are 50–271 (USFWS, 2012a). Jaguars there face heavy human-induced mortality (Rosas-Rosas, 2006), and the effect of hunting on prey is also of concern (Brown & López-González, 2001). Zeller (2007) estimated that only 4% of jaguar habitat in Sonora receives some protection.…”
Section: The Northern Jaguar Populationmentioning
confidence: 99%
“…Sonora has the northernmost population of jaguars, which has been estimated by researchers at a density of 1.05-1.1/100 km 2 (Gutierrez-Gonzalez et al, 2012;Rosas-Rosas and Bender, 2012) and is considered to be one of the lowest reported in the literature for all jaguar distribution (Maffei et al, 2011). A few jaguars still disperse into the southwestern United States, where they are legally protected as an endangered species (Fish and Wildlife Service, Interior, 1997).…”
mentioning
confidence: 99%